Production of cellulase enzyme by solid state bioconversion on agricultural waste using Trichoderma species - Hasan Khan, Mohammad Maifi; Ali, Salmiaton; Ahmadun, Fakhru'l-Razi; Alam, Md Zahangir (Federation of Engineering Institutions of Islamic Countries, 2006)
Cellulase production was carried out by solid state bioconversion using rice straw, an agricultural waste, as the substrate of three Trichoderma spp. in lab-scale experiments. The results were compared to select the best fungi among them for the production of cellulase. Trichoderma harzianum was found to be the best among the three species, which produced the highest cellulase enzyme of of 0.77 IU/ml of filter paper activity and 1.88 IU/ml of carboxymethyl cellulose activity. The glucosamine and reducing sugar parameters were observed to evaluate the growth and substrate utilization in the experiment and pH was also recorded.